The unintended side effects of regulating charities: Donors penalise administrative burden almost as much as overheads - Margaret Samahita; Leonhard K. Lades (University College Dublin, UCD Centre for Economic Research, 2021)
Recent experimental evidence suggests that donors are averse to giving to charities with high overhead ratios. This paper asks whether donors are also averse to giving to charities spending a high share of the donations on unavoidable administrative expenses. The results of an experiment with a nationally representative sample (n = 1, 032) suggest that donors dislike paying for administrative burden almost as much as for overhead. While donors care primarily about how much of their donations are used for program-related services, donors seem to have a weak preference for charities to spend their donations on administrative burden rather than on overheads. Government subsidies that help alleviate charities' administrative burden can reduce donors' aversion to give to charities with high administrative expenses. Overall, we show that regulations that aim to increase transparency and accountability in the charity sector can have the unintended side effect of reducing charitable giving.
hdl:10197/11955
Keywords: C99; D64; L31; 330; charitable giving; administrative burden; overhead aversion; information; dictator game; online experiment